2002
DOI: 10.1186/1471-2334-2-3
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, cross-sectional study of anaemia and peripheral iron status in antiretroviral naïve, HIV-1 infected children in Cape Town, South Africa

Abstract: Background: Anaemia is a common manifestation of paediatric HIV infection. Although there are many causes, anaemia of chronic diseases is the most frequent type. In poor countries iron deficiency is widespread. It is probable that many HIV-infected children in these countries are also iron deficient. This study describes the relationship between paediatric HIV infection and anaemia, and documents the peripheral iron status of antiretroviral naive, HIV-infected children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
27
1
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 15 publications
9
27
1
5
Order By: Relevance
“…Before initiation of ART in children, anemia in this study (54.4%) was almost as prevalent in the subjects as in a similar study done in Jimma, Ethiopia (53.1%),7 but it was less common than in reports from India (66%) and South Africa (73%) 12,13. Prevalence of anemia was higher among the preschool children in the current study.…”
Section: Discussionsupporting
confidence: 50%
“…Before initiation of ART in children, anemia in this study (54.4%) was almost as prevalent in the subjects as in a similar study done in Jimma, Ethiopia (53.1%),7 but it was less common than in reports from India (66%) and South Africa (73%) 12,13. Prevalence of anemia was higher among the preschool children in the current study.…”
Section: Discussionsupporting
confidence: 50%
“…Few studies among HIVinfected children have comprehensively examined the causes of anemia in this population. In the South African study where ferritin<10 μg/dl was used to define iron depletion, 45% of all anemic toddlers were found to be iron depleted, although the remaining causes of anemia were not studied [9]. Interestingly in this study, the prevalence of iron deficiency alone was also high at 52%.…”
Section: Anemia and Nutritional Deficienciesmentioning
confidence: 66%
“…A Ugandan study among ART-naive young infants with HIV reported that 92% had anemia at baseline, and 100% developed anemia over the succeeding 3 years [6]. A study of HIV-infected toddlers between ages 1 and 3 years in South Africa reported an anemia prevalence of 73% [9], while a Malawian study indicated that 78% of 12-month-old HIV-infected infants had anemia [40]. The inclusion of children older than 2 years and the presence of ART may explain the lower prevalence of anemia seen in our study.…”
Section: Anemia and Hiv Infectionmentioning
confidence: 96%
“…31 Iron deficiency is highly prevalent (18.0-44.3%) in developing countries, 3,29 but not in this study. The high prevalences of IDA in other studies might be the result of the inclusion of children with poorer nutritional status and more severe clinical stage of HIV.…”
Section: Discussionmentioning
confidence: 83%
“…13 IDA [3][4][5][6][7][8][9][10][11][12][13][14][15] was defined as anemia with (1) serum ferritin < 10 lg/ml if CRP was < 10 mg/liter or serum ferritin < 50 lg/ml if CRP was ‡ 10 mg/liter 16,17 and (2) having at least three of the following five parameters: (1) SI < 8.8 lmol/liter, (2) TIBC > 71.6 lmol/liter, (3) TS < 10%, (4) mean corpuscular volume (MCV) less than normal age-related values ( < 2 years = 78 fl, ‡ 2 years = 81 fl), or (5) mean corpuscular hemoglobin (MCH) less than normal age-related values ( < 2 years = 23 pg, 2-5 years = 24 pg, and ‡ 6 years = 25 pg). 14,15 Nonthalassemia was defined as having no common thalassemia mutations or deletions of a-and b-genes.…”
Section: Methodsmentioning
confidence: 99%